Chemotherapy and radiotherapy use in patients with lung cancer in Australia, Canada, the UK and Norway 2012–2017: an ICBP population-based study - Andriana Barisic; Samantha Harrison; David Baldwin; Sean McPhail; Georgios Lyratzopoulos; Matthew E Barclay; Laura Downie; Richard Walton; Bin Zhang; Mark Lawler; John Butler; Oliver Bucher; et al. (BMJ Oncology)
Background International variation in lung cancer survival may be partly explained by variation in stage-specific treatment use, but relevant comparative evidence is sparse. As part of the International Cancer Benchmarking Partnership, we examined use of chemotherapy and radiotherapy in population-based cancer registry data.Methods Linked population-based data sources were used to describe use and time to first treatment for either chemotherapy or radiotherapy in patients with lung cancer diagnosed in study periods during 2012–2017 in 16 jurisdictions of Australia, Canada, the UK and Norway.Results There was large variation in the proportions of patients with lung cancer receiving chemotherapy (ranging from 23% in Northern Ireland to 45% in Norway) and radiotherapy (ranging from 32% in England to 48% in New South Wales and 50% in Newfoundland and Labrador). Across jurisdictions, chemotherapy use decreased steeply with increasing age, regardless of stage at diagnosis. For radiotherapy use, in stage 1–3 cancer three patterns were observed: (a) steep decrease with increasing age (UK jurisdictions, Saskatchewan-Manitoba); (b) a relatively flat pattern (Norway, Alberta, British Columbia, Atlantic Canada, New South Wales) and (c) increasing use with increasing age (Ontario).Time to radiotherapy initiation was longer in the UK jurisdictions than elsewhere; time to chemotherapy was longer in the UK and Canadian jurisdictions except Ontario.Discussion Use of chemotherapy and radiotherapy in patients with lung cancer varied substantially between jurisdictions during the mid-2010s within age-stage strata. Reasons for these variations are unclear. Differences in non-surgical treatment use are plausibly associated with international variation in lung cancer survival.